Social movements and social transformation - Rao, M.S.A. (Delhi, 1979)
This is a study of two backward classes movements-Sri Narayana Dharma Paripalana movement (Movement for the Propagation of the Philosophy of Sri Narayana Guru Swamy) and the Yadava movement-in India, in the wider context of the sociology of social movements. An attempt is made to present a social movement approach to the study of social change in moderr India in contrast to the established imitative process of change. While the latter considers changes as mainly positional, occurring through processes of imitation and gentlemanly passing, the former posits protest and confliet as crucial in effecting structural changes. Backed by an ideology of relative deprivation, committed leadership and a federal type of organizational framework, linking local and regional associations for collective mobilization, the two movements described in this book have led to social transformation ', representing middle-scale structural and organizational changes between reform ? on one hand and 'revolution' on the other. Social mobility in this context occurs as part of wider transformative changes through protest, aggression, confrontation and conflict, and by way of wresting power and monopoly in the use of different kinds of goods and services-religious, educational, economic and political-from the forward classes' who formed the first class citizens of India for thousands of years.
Keywords: Social change